Compaction of ultra-fine Al powders. (24th March 2005) - Balog, Martin; Nagy, Juraj; Izdinsky, Karol; Simancik, Frantisek
The possibility of preparing bulk sub-micron grained profiles with superior mechanical properties was investigated. A bottom-up route was used, wherein commercial ultra-fine powders were consolidated with the aim of preserving the initial fine-grained structure and thus obtain unique mechanical properties. A relatively simple and cheap technique for preparation of Al bulk profiles through conventional direct extrusion compaction was established. During extrusion initial powder particles were deformed and fragmentised into ultra-fine elongated grains mostly aligned along the extrusion direction. Moreover, extensive energy induced into the input powder during compaction yielded fine distorted oxide dispersoids homogenously distributed within the final compacts. These do in fact represent MMC where Al matrix is reinforced with nanoscale alumina particles. The influence of powder size and other processing parameters on consolidation behaviour and mechanical properties of compacted profiles, their structure and thermal stability are reported and discussed. Overall comparison with conventionally prepared SAP materials is made.